Which factors promote and prohibit successful implementation and normalization of a healthy school lunch program at primary schools in the Netherlands? - Ellen van Kleef; S. Coosje Dijkstra; Jaap Seidell; Monique H. Vingerhoeds; Ilse A. Polet; Gertrude G. Zeinstra (Journal of Health, Population and Nutrition, 2022)
Abstract Background A school provided healthy lunch might help to improve the nutritional quality of children’s lunches. However, in the Netherlands, school lunch programs are not common. The aim of this study was to identify factors that promote or inhibit the implementation of a school lunch program at primary schools, from the viewpoint of school professionals. Methods A cross-sectional online survey was conducted among 204 primary school professionals. The normalization process theory and its four constructs (i.e. coherence, cognitive participation, collective action, reflective monitoring) were used to develop questions and interpret findings. Descriptive statistics were used for 14 multiple choice questions (yes, no, don’t know) and thematic content analysis for qualitative responses. Results Participants had a shared understanding about how a lunch program differed from current practices. Most participants had the same view on the rationale for implementation (coherence), such as equality among children. Sixty percent expected that a healthy school lunch will contribute to healthier eating by the children. Participants showed different degrees of cognitive participation (46% indicated that healthy school lunch is good idea). Commitment depended on their belief whether providing a healthy lunch was part of their responsibility as school and 30% expected a large effect on their daily work (collective action). When appraising school lunch implementation (reflective monitoring), participants’ concerns focused on feasibility and adaptability of a program in their own school. Conclusions The introduction of a school lunch program will require substantial effort, although there is considerable support and understanding about potential benefits. The findings point to a number of preconditions for large-scale introduction, including the need for support—both financially and organizationally—bottom-up involvement of teachers, children and parents and freedom to adapt the program.